Children often present with infantile spasms after herpetic encephalitis. Issue 9 (1st July 2013) - Aznar Laín, Gemma; Dellatolas, Georges; Eisermann, Monika; Boddaert, Nathalie; Chiron, Catherine; Bulteau, Christine; Monteiro, José P.; An, Isabelle; Pédespan, Jean‐Michel; Cancès, Claude; Peudenier, Sylvianne; Barthez, Marie‐Anne; et al.
Summary Purpose To determine what epilepsy types occur after herpetic encephalitis and what are the determinant factors for subsequent infantile spasms. Methods We analyzed retrospectively the clinical history of 22 patients, referred to Necker and Saint Vincent de Paul Hospitals (Paris) through the French pediatric epilepsy network from March 1986 to April 2010 and who developed epilepsy some months after herpetic encephalitis. We focused on seizure semiology with video–electroencephalography (EEG) recording, and on neuroradiology and epilepsy follow‐up. Key Findings Fourteen patients developed pharmacoresistant spasms, and eight developed focal epilepsy, but none had both. The patients who developed spasms were more frequently younger than 30 months at age of onset of epilepsy and had herpetic encephalitis earlier (mean 10.6 months of age) than those who developed focal epilepsy (mean 59.7 and 39.6 months, respectively). Epilepsy follow‐up was similar in both groups (8.5 and 11 years, respectively). We found 26 affected cerebral areas; none alone was related to the development of epileptic spasms. Significance Risk factors to develop epileptic spasms were to have had herpetic encephalitis early (mean 10 months); to be significantly younger at onset of epilepsy (mean 22.1 months); and to have cerebral lesions involving the insula, the hippocampus, and the temporal pole.